Pädagogische Hochschulentwicklung: Von der Programmatik zur Implementierung - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
Der Sammelband befasst sich mit einem umfassenden Ansatz zur Verbesserung der Qualität von Lehre und Studium. Mit dem Konzept der pädagogischen Hochschulentwicklung plädieren die AutorInnen dafür, bei der Umsetzung von Veränderungsprojekten die verschiedenen Ebenen der Hochschule zu verschränken. Zum Beispiel sollten Initiativen, die eine Lehrveranstaltung betreffen, idealerweise die (Aus )Wirkungen auf den Ebenen der Studienprogramme und der Organisation berücksichtigen und aktiv gestalten. Die einzelnen Beiträge stellen beispielhafte Initiativen aus unterschiedlichen Disziplinen und Hochschulformen dar und illustrieren, wie die genannten Ebenen in der praktischen Umsetzung verzahnt werden können.

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari
Starting with this issue, the ZFHE will publish one English-speaking edition per year on a topic of international interest, in order to disseminate German-language research results beyond our borders and to encourage discussion in an international context. This first English-language edition focuses on the experiences and the academic socialization of first-year university students. The articles offer both diagnoses and differentiations in terms of different types of first-year students, as well as highlighting their experiences and development during their introduction to the academic environment and examining connections between their academic development and the existing educational environment.

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

How Do They Find Their Place? A Longitudinal Study of Management Students' Attitudes and Motivations During Their First Year at Business School - Jenert, Tobias; Brahm, Taiga
The first year of studying has been extensively researched applying different theoretical lenses to better understand the transition into Higher Education (HE). It is of particular interest to investigate how students deal with frictions between themselves as individuals and what they perceive to be dominant features of the first-year culture of their studies. To tackle this question, a qualitative longitudinal study was conducted. Based on a sociocultural understanding of attitudes and motivations, its aim was to closely follow a relatively small but highly diverse sample of students throughout their first year at a business school in order to develop an in-depth understanding of each individual’s motivational and attitudinal development.
Keywords: Enculturation; first-year students; beginning students; retention; drop-out

The crucial first year: Students’ motivation at a Swiss Business School--a longitudinal study - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Academy of Management Proceedings)
Despite students’ motivation being considered a strong predictor of performance, the development of motivation of business school students has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. This is surprising, as the transition from school to university is a crucial phase in the academic career and can be overwhelming for some students. The present study addresses this research gap and examines the development of economics and management students’ study motivation. The longitudinal study included four waves of data collected throughout the first year using quantitative surveys. Regarding students’ development over time, the analysis showed a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline

Zwischen Individuum, Institution und Disziplin: Methodologische Überlegungen zur Erfassung von Lernkulturen an Hochschule - Jenert, Tobias; Reinmann, Gabi (Dokumentation der Jahrestagung der Sektion Erwachsenenbildung der DGfE)
Keywords: Methodologie; Lernforschung; hochschuldidaktische Forschung; Higher Education

Zwischen" netten" Tools und" Überdidaktisierung": Neue Medien in der Hochschuldidaktik - Wagner, Dietrich; Jenert, Tobias
Auswertung einer Befragung unter Studierenden zu der Frage welche Elemente eine Lehrveranstaltung innovativ machen und welche Rolle die neuen Medien dabei spielen. Digitale Medien begegnen uns in der Hochschule immer wieder. Häufig handelt es sich um neue Werkzeuge oder Trends (Klicker, MOOCs, Web 2.0), die einerseits potenzialreich und spannend erscheinen, deren didaktische Verwertbarkeit sich aber nicht auf den ersten Blick erschließt. Oft folgt nach einer euphorischen Erprobung schnell die Ernüchterung, wenn festgestellt wird, dass sich durch die digitalen Technologien allein kein erhöhter Lernerfolg ergibt und auch die Studierenden keine nachhaltigen Motivationsschübe erfahren. Aus der Hochschuldidaktik hört man häufig und berechtigterweise kritische Stimmen, welche die Einbettung digitaler Medien in sorgfältig geplante didaktische Arrangements betonen. Es stellt sich die Frage, inwieweit damit die Kreativität und der Entdeckergeist von Lehrenden und Studierenden eingeschränkt werden. Wir wollen im Disq-Space der Frage nachgehen, wie die Hochschuldidaktik auf neue digitale Trends reagieren und dabei einen Mittelweg zwischen "kreativem Ausprobieren" und pädagogisch-didaktischer Rationalität einschlagen kann. Zunächst werden die Ergebnisse einer aktuellen Umfrage an der Universität St. Gallen zu den Vorstellungen Studierender zu innovativer Lehre vorgestellt. Nach einer Öffnung des Raums für gute sowie schlechte Erfahrungen und Bespiele von Seiten der Teilnehmenden soll diskutiert werden, welche personellen, didaktischen und organisatorischen Voraussetzungen erfüllt sein müssen, damit Digitalisierung die Kompetenzentwicklung der Studierenden unterstützt. Die Ergebnisse der Diskussionsrunde werden im Blog des Teams Hochschulentwicklung zur Verfügung gestellt. Es wird angestrebt, diese damit einer breiteren Öffentlichkeit zugänglich zu machen.
Keywords: Neue Medien; Hochschuldidaktik; Studierende; Innovation in der Lehre

On the iterative plug-in algorithm for estimating diurnal patterns of financial trade durations - Feng, Yuanhua; Forstinger, Sarah; Peitz, Christian (Journal of Statistical Computation and Simulation)

Forecasting financial market activity using a semiparametric fractionally integrated Log-ACD - Feng, Yuanhua; Zhou, Chen (International Journal of Forecasting)